Perbandingan Mikroorganisme Pada Kultur Urin Pre-Operasi Dan Kultur Batu Pasca Operasi Pada Pasien Batu Saluran Kemih - Indra Jaya; Gatot Aji Prihartomo; Fathiyah afaf (Fakultas Kedokteran Universitas Riau, 2023)
Urinary tract infection (UTI) and urinary tract calculi (UTC) still causes significant health problem and present as a dominant case in urology. Urine culture is a standard examination prior to UTC surgery which provide information on microorganism and its sensitivity to antibiotics. Despite of appropriate preoperative antibiotic therapy, we still found post operative infections among those patients. This study aims to determine if there any difference between urine and calculi culture in patients underwent UTC surgery. This is a comparative observational study in patients underwent urinary stone removal procedures from April 2022 to August 2022. Urinary culture attained 5-7 days prior to procedure and crushed calculi culture directly after procedure. The comparison between two examinations was performed. Total of 50 cases consisting of 33 (66%) males and 17 (34%) females was included. Patient with positive urine culture and calculi culture was 15 (30%) and 14 (28%) respectively. Only 3 (6%) patients positive for both, and only one patient with same pathogen. In 11 (22%) patients, we found positive calculi culture with previously sterile urine culture. Most common pathogen in urine culture was Escherichia coli, and Klebsiella pneumoniae found mostly in calculi culture. This study showed 21% accuracy, 66,67% specificity, 20% positive prediction value, 68,57% negative prediction value and 54% diagnostic accuracy. Low positive prediction value and diagnostic accuracy for microorganism of preoperative urine cultured was shown in this study. As a consequences, calculi culture is required as a routine examination during stone removal procedures.